Empowering rural economies through women-led tourism enterprises in local development - Thaqi, Nora Vizdik; Thaqi, Agim (Edelweiss Applied Science and Technology, 2025)
This study explores the role of women-led businesses in the economic development of rural tourism, focusing on identifying both challenges and opportunities. Based on structured survey data collected from women entrepreneurs in a rural context, the research evaluates the impact of their entrepreneurial activities on tourism growth and local development. The results highlight significant barriers faced by women, including limited access to start-up capital, ongoing financial constraints, and restrictive cultural norms. Despite these obstacles, the study finds that women-owned enterprises play a vital role in promoting cultural heritage, enhancing local tourism experiences, and supporting agricultural-based tourism initiatives. These contributions not only foster economic growth but also reshape the social and professional identities of women in rural communities. The study concludes that targeted support from governmental institutions, civil society, and local stakeholders is essential to overcome structural limitations and empower women entrepreneurs. The findings offer valuable insights into the socio-economic and cultural dynamics influencing rural tourism and underscore the need for inclusive development strategies that recognize and strengthen the role of women in rural entrepreneurship.